The Influence of Occupational Health and Safety (K3) and the Work Environment on Employee Productivity at PT. KGS - Apriliana, Hana; Sudinta, Heru; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to analyze the influence of Occupational Health and Safety (OHS) and the work environment on employee productivity at PT KGS. Employee productivity is an important factor in supporting the achievement of company goals, which is influenced by safe, healthy, and comfortable working conditions. The research method used is a quantitative method with a survey approach. Data were collected through distributing questionnaires to PT KGS employees and analyzed using multiple linear regression analysis. The results of the study indicate that Occupational Health and Safety (OHS) has a positive and significant effect on employee productivity. In addition, the work environment also has a positive and significant effect on employee productivity. Simultaneously, both OHS and the work environment have a significant effect on employee productivity at PT KGS. Thus, the implementation of a good OHS program and the creation of a conducive work environment can increase employee productivity. This research is expected to be a consideration for company management in improving employee performance and welfare.